Dampak Residu Pestisida Terhadap Keanekaragaman Jamur Tanah Pada Lahan Sayuran: Impact of Pesticide Residues on the Diversity of Soil Fungi on Vegetable Land - Martha Maria Magdalena Benu; Anthonius S. J. Adutae; Lince Mukkun (Jurnal Ilmu Tanah dan Lingkungan, 2020)
Insecticides have a negative effect on soil fungi because they contain dangerous toxic compounds. The use of insecticides by Noelbaki village farmers in vegetable cultivation is quite intensive with, a frequency of 2-3 spraying per week. The application of this insecticide is carried out continuously during the planting of vegetables so that it has a negative impact on the soil environment. This study aimed to determine the content of insecticide residues and the diversity of soil fungi in mustard vegetable fields. The research method used was a survey method conducted on several mustard vegetable farmers by collecting information using a questionnaire as a means of collection data and laboratory tests of residue content in the soil. Soil samples were taken using a diagonal pattern with 5 replications on mustard greens on Vertisols and Inceptisols both applied and without insecticides. Soil samples in a composite soil were carried out for the analysis of residual content and physical and chemical properties of the soil, while not composist was used for the observation of soil fungi. The variables observed were the content of insecticide residues, population density, diversity and frequency of presence, soil fungi and the physical and chemical properties of soil on the vegetable land. Analysis of insecticide residues was carried out using the Gas Chromatography-Spectrometry Mass (GC-MS/ MS) method, and the counting of microbes was carried out using the Plate Counting Agar (PCA) method, while the identification of microbes was carried out by microscopic and macroscopic observations. Insecticide residues with the active ingredient Lamda-cihalotrin in the Vertisol type soil samples treated with insecticides were 0.060 ppm, and in the Inceptisol soil samples with the active ingredient Dimetoat as much as 0.042 ppm. The density of soil mushroom population was higher in vegetable fields without the application of Insecticides as much as 71.6 CFU g-1, the value of soil mushroom diversity index was higher in insecticide application vegetable fields 1.609, the frequency of presence of the fungus species Penicillium constant 100% and Mucor 90%.